The influence of annealing temperature and tellurium (Te) on electrical and dielectrical properties of Al/p-CIGSeTe/Mo Schottky diodes - Kompitsas, M.; Fiat, S.; Cankaya, Güven; Polat, I.; Bacaksiz, E. (Elsevier BV, 2013)
Abstract p-CuIn 0.7 Ga 0.3 (Se (1− x ) Te x ) 2 type thin films were synthesized by thermal evaporation method on Mo coated glass substrates. To obtain Al/CuIn 0.7 Ga 0.3 (Se (1− x ) Te x ) 2 /Mo Schottky diode structure for two compositions of x  = 0.0 and 0.6, Al metal was evaporated on upper surface of CuIn 0.7 Ga 0.3 (Se (1− x ) Te x ) 2 as a front contact. Al/p-CuIn 0.7 Ga 0.3 (Se (1− x ) Te x ) 2 /Mo structures were annealed temperature range from 150 °C to 300 °C for 10 min under vacuum. The electrical and dielectrical properties of Al/p-CuIn 0.7 Ga 0.3 (Se (1− x ) Te x ) 2 (CIGSeTe) Schottky barrier diodes (SBD) have been investigated. Capacitance–Voltage ( C – V ) characteristics, Conductance–Voltage ( G / w – V ) characteristics and interface state density were studied in order to obtain electrical and dielectrical parameters. The effects of interface state density ( N ss ), series resistance ( R s ), the dielectric constant ( ɛ ′), dielectric loss ( ɛ ″), dielectric loss tangent (tan  δ ), ac electrical conductivity ( σ ac ) and carrier doping densities were calculated from the C – V and G / w – V measurements and plotted as a function of annealing temperature. It was observed that the values of carrier doping density N A for annealing temperature at 150 °C decreased from 2.83 × 10 +15  cm −3 to 2.87 × 10 +14  cm −3 with increasing Te content from x  = 0.0 to 0.6. The series resistance for x  = 0.0 found to be between 10 and 75 Ω and between 50 and 230 Ω for x  = 0.6 in the range of annealing temperature at 150–300 °C.
Keywords: Dielectrical properties; Physical and theoretical chemistry; Electrical properties; Φυσική και θεωρητική χημεία; Chalcopyrite compounds; CIGSeTe; 7. Clean energy